Follow Your Heart: How Is Willingness to Pay Formed under Multiple Anchors? - Lin, Chien-Huang; Chen, Ming (Frontiers in Psychology, 2017)
In sales, a common promotional tactic is to supplement a required purchase (i.e., a focal product) by offering a free or discounted product (i.e., a supplementary product). The present research examines the contextual factors driving consumer evaluations of the supplementary product after the promotion has been terminated. Two experiments are used to demonstrate that consumers use multiple anchors to determine the value of a supplementary product. Consumers use other types of price information, such as the internal reference price, promotional price and original price of the supplementary product, as anchors to adjust their willingness to pay. Among the multiple anchors, the consumer’s internal reference price is not only the crucial anchor to estimate the willingness to pay but also the criterion to determine whether other price information can serve as anchors. Price information, such as the promotional and original price of the supplementary product, which is higher (lower) than the internal reference price, will increase (decrease) the willingness to pay. However, these anchors are only employed when the price information is considered to be plausible. Assimilation and contrast effects occur when the internal reference price is used by consumers as a criterion to judge the reasonableness of other anchors. When the external price information belongs (does not belong) to consumers’ distribution of internal reference price, assimilation (contrast) effects occur, and consumers will regard the external reference price (ERP) to be a plausible (implausible) price. Limitations and future avenues for research are also discussed.